Caracterización y tipificación de la avicultura de traspatio en Boyacá, Colombia, y su efecto sobre la seguridad alimentaria - Hortúa-López, Laura (2022)
Backyard poultry farming is a traditional productive practice of family farming that contributes to family nutrition, female empowerment and cohesion in the territories. The objectives of this study were to characterize and classify the backyard poultry farming systems (BPS) in the peri-urban area of Tunja (Boyacá-Colombia) and to determine their contribution to the dimensions of food security. Sociocultural, socioeconomic, technical and planning variables were used. The perception of food insecurity of the participants was analyzed using the Latin American and Caribbean Food Security Scale. In total, 138 BPS from 11 municipalities of Boyacá were typified through cluster analysis of mixed data. The BPS were characterized by being in charge of older adult women with low levels of schooling, mainly owning farms of less than 5 ha. The birds are kept with poor management practices, poor infrastructure and poor health care. The BPS can be classified into three categories: 1) BPS-traditional self-consumption (40.5%); 2) BPS-traditional sales and self-consumption (44.2%); and 3) BPS-in transition (13.7%). Backyard poultry farming contributes to the dimensions of food security, since it favors the availability and direct access to foods of high biological value, such as chicken meat and eggs, allowing this type of food to reach remote places, where the quality of life of its inhabitants is low based on the relationship between housing conditions, the size of the properties and access to public services.